2022
DOI: 10.1002/cam4.4645
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumor markers level and their predictive values for solid and micropapillary components in lung adenocarcinoma

Abstract: Background: This study aims to reveal the serum tumor marker (STM) levels in lung adenocarcinoma (LUAD) histological subtypes and evaluate their values in predicting the solid and micropapillary components (SMC). Methods:We retrospectively analyzed 3100 invasive LUAD patients between January 2017 and December 2020. Associations between preoperative STMs (CEA, CYFRA21-1, CA199, CA724, NSE, AFP) and LUAD subtypes were evaluated. Multivariate regression analyses were used to determine the independent predictors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
3
3
0
Order By: Relevance
“…The predictors in the model included CTR, lobulation, smoking history, and CEA level, and similar results have been shown in previous studies [ 27 30 ]. Chen et al defined CTR > 0.5 as radiological invasiveness and used it to construct a radiomics model for predicting micropapillary and solid components, with the sensitivity and specificity reaching 90.00% and 45.21%, respectively [ 27 ].…”
Section: Discussionsupporting
confidence: 79%
“…The predictors in the model included CTR, lobulation, smoking history, and CEA level, and similar results have been shown in previous studies [ 27 30 ]. Chen et al defined CTR > 0.5 as radiological invasiveness and used it to construct a radiomics model for predicting micropapillary and solid components, with the sensitivity and specificity reaching 90.00% and 45.21%, respectively [ 27 ].…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, TVR being an important independent prognostic factor in LACC patients, its value in different FIGO stage-groups needed to be veri ed. Serum albumin level, commonly used to assess nutritional status, is also an important prognostic factor for advanced cancer and merits inclusion in prognostic subgroup analyses [18][19][20]. Our ndings not only demonstrate that FIGO stage and pre-treatment albumin are independent prognostic factors in LACC patients, but also con rm that TVR has signi cant prognostic value different subgroups based on the FIGO stage and pre-treatment albumin levels.…”
Section: Analysis Of Different Risk Subgroups Of Lacc Patientssupporting
confidence: 51%
“…In addition, we have shown that although the CEA concentration and tumor size are independent indicators of the presence of a micropapillary component, their AUCs are low. This may be because of the inclusion of patients in the micropapillary-negative group with a solid component to their tumor, given that there is abundant evidence that the presence of a solid tumor component is often associated with a high CEA concentration 30 and a large tumor. 26 Therefore, in future research, we intend to create more appropriate groups to more accurately evaluate the use of the CEA concentration and tumor size as potential indicators.…”
Section: Discussionmentioning
confidence: 99%